Investigation of the effect of electric heating of expanded clay concrete mixture on the structure and properties of lightweight expanded clay concrete exposed to high temperatures - G. N. Khadzhishalapov; T. A. Khezhev; A. M. Gadzhiev; R. G. Radjabov; U. I. Isaeva (Вестник Дагестанского государственного технического университета: Технические науки, 2022)
Objective. The aim of the study is to study the effect of preliminary electrical heating of the concrete mixture on the structure and properties of heat-resistant expanded clay concrete on a composite binder before drying at a temperature of 105°C. Method. It is based on domestic and foreign experience in studying the effect of preliminary electrical heating on the properties and structure of various concretes, including heat-resistant ones. Result. A laboratory stand for preliminary electrical heating of mixtures has been developed and tested. The influence of preliminary electric heating on the process of self-steaming of heat-resistant expanded clay concrete has been studied. A mode of preliminary electric heating of a heat-resistant expanded clay concrete mixture in time has been developed. Stress dependences are obtained due to the difference in the temperature coefficients of linear expansion of coarse and fine aggregates and the mortar part on the heating temperature, as well as the dependences of the ultimate strength of expanded clay concrete on the heating temperature of the expanded clay concrete mixture under various modes of preheating with a composite binder with a ratio of components: Portland cement 70%, mineral additive 30%. Conclusion. Based on the results obtained and the analysis of the studies carried out in the field of preliminary electrical heating of concrete mixtures, it can be concluded that the preliminary electrical heating of a mixture for heatresistant concrete with expanded clay filler based on an activated composite binder will make it possible to obtain concrete with higher physico-thermal and operational characteristics, as well as to reduce the technological process of manufacturing heat-resistant products, the drying period and bringing the thermal unit to the operating mode.